A Geospatial Analysis of Severe Firearm Injuries Compared to Other Injury Mechanisms: Event Characteristics, Location, Timing, and Outcomes. (15th April 2016) - Newgard, Craig D.; Sanchez, Brittany J.; Bulger, Eileen M.; Brasel, Karen J.; Byers, Adam; Buick, Jason E.; Sheehan, Kellie L.; Guyette, Frank X.; King, Richard V.; Mena‐Munoz, Jorge; Minei, Joseph P.; Schmicker, Robert H.; et al.
Abstract: Objectives: Relatively little is known about the context and location of firearm injury events. Using a prospective cohort of trauma patients, we describe and compare severe firearm injury events to other violent and nonviolent injury mechanisms regarding incident location, proximity to home, time of day, spatial clustering, and outcomes. Methods: This was a secondary analysis of a prospective cohort of injured children and adults with hypotension or Glasgow Coma Scale score ≤ 8, injured by one of four primary injury mechanisms (firearm, stabbing, assault, and motor vehicle collision [MVC]) who were transported by emergency medical services to a Level I or II trauma center in 10 regions of the United States and Canada from January 1, 2010, through June 30, 2011. We used descriptive statistics and geospatial analyses to compare the injury groups, distance from home, outcomes, and spatial clustering. Results: There were 2, 079 persons available for analysis, including 506 (24.3%) firearm injuries, 297 (14.3%) stabbings, 339 (16.3%) assaults, and 950 (45.7%) MVCs. Firearm injuries resulted in the highest proportion of serious injuries (66.3%), early critical resources (75.3%), and in‐hospital mortality (53.5%). Injury events occurring within 1 mile of a patient's home included 53.9% of stabbings, 49.2% of firearm events, 41.3% of assaults, and 20.0% of MVCs; the non‐MVC events frequently occurred at home. While there was geospatial clustering, 94.4% of firearm events occurred outside of geographic clusters. Conclusions: Severe firearm events tend to occur within a patient's own neighborhood, often at home, and generally outside of geospatial clusters. Public health efforts should focus on the home in all types of neighborhoods to reduce firearm violence.